ENVIRONMENTAL AND GREEN ACCOUNTING PRACTICES AND FINANCIAL PERFORMANCE: INDONESIAN LISTED MANUFACTURERS - Tesalonika, May; Samosir, Hendrik E.S; Dolok Saribu, Ardin (Univesitas Muhammadiyah Tangerang, 2025)
This study examines the impact of green accounting and environmental performance on financial performance, focusing on mining-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2021 to 2023. Using purposive sampling, 30 firms met the inclusion criteria. The research employs quantitative methods with secondary data collected from annual financial reports and sustainability disclosures. Green accounting is measured by environmental costs, while environmental performance is proxied by the PROPER (Program for Pollution Control, Evaluation, and Rating) rating. Financial performance is assessed using Return on Assets (ROA). Data analysis using SmartPls 3.0. The results indicate that green accounting has no significant effect on financial performance, and environmental performance does not significantly influence financial outcomes. The coefficient of determination (R²) reveals that the independent variables explain only 1% of the variation in financial performance, suggesting that other factors play a more dominant role. These findings imply that current environmental cost reporting and regulatory ratings like PROPER may not yet translate into measurable financial benefits for mining-related manufacturers in Indonesia. The study contributes to the growing literature on sustainability accounting in emerging markets, highlighting the gap between environmental initiatives and financial returns. Future research should incorporate additional variables such as ESG scores, corporate governance, or carbon emissions, and extend the time frame and sample size to enhance generalizability.